Hitting for Average: Educational Assessment, Unidimensionality, and the Connection to Baseball Hitting Statistics - Alex Romagnoli (Educational Considerations, 2024)
The traditional points system and subsequent Grade Point Average (GPA) in education perpetuates an evaluation of academic performance which reflects arbitrary weighting of assignments and/or assessments. As such, GPAs which are calculated using a traditional points system are not unidimensional in their design. The baseball batting and slugging percentage, which serves as established metrics for performance evaluations among baseball players, better reflects unidimensionality. In essence, this paper puts forth an analysis and discussion which posits that baseball batting average and slugging percentage can serve as an example for how unidimensionality can become more prevalent in educational assessments, especially as it relates to the traditional points system and GPA.
Keywords: Assessment; unidimensionality; baseball; Grade Point Average (GPA); education